Schooling and Labor Market Effects of Temporary Authorization: Evidence from DACA - Catalina Amuedo-Dorantes; Francisca M. Antman (Institute for the Study of Labor (IZA), 2016)
This paper explores the labor market and schooling effects of the Deferred Action for Childhood Arrivals (DACA) initiative, which provides work authorization to eligible immigrants along with a temporary reprieve from deportation. The analysis relies on a difference-in-differences approach that exploits the discontinuity in program rules to compare eligible individuals to ineligible, likely undocumented immigrants before and after the program went into effect. To address potential endogeneity concerns, we focus on youths that likely met DACA's schooling requirement when the program was announced. We find that DACA reduced the probability of school enrollment of eligible higher-educated individuals, as well as some evidence that it increased the employment likelihood of men, in particular. Together, these findings suggest that a lack of authorization may lead individuals to enroll in school when working is not a viable option. Thus, once employment restrictions are relaxed and the opportunity costs of higher-education rise, eligible individuals may reduce investments in schooling.
Keywords: J15; J61; J2; J3; 330; undocumented immigrants; work authorization